Dental development in cleft lip and palate patients: A systematic review. (July 2019) - Van Dyck, Julie; Cadenas de Llano-Pérula, Maria; Willems, Guy; Verdonck, Anna
Highlights: The majority of the included articles reported a delay in tooth development or -eruption in CLP patients. A mean delay of 0.56 years was found for all types of clefts. The lateral incisor at the cleft side was generally the most delayed. The teeth near the cleft showed a greater delay than the teeth further away from it. An increased risk of asymmetrical tooth development in CLP patients was observed. Abstract: Objective: To investigate a potential delay in dental development in cleft patients compared with non-cleft patients. Search methods: An unlimited electronic search was performed in four databases (PubMed, Embase, Lilacs and OpenGrey), from inception until October 2018. Full text articles concerning dental development or tooth eruption of non-syndromic children with cleft lip and/or palate (CL(P)) were included and reviewed. Case reports/series, review articles, articles in languages other than English, Dutch, French or Spanish and studies considering the eruption of deciduous teeth were excluded. Data extraction followed the PRISMA guidelines and study quality was assessed using MINORS. Results: The primary search resulted in 991 citations, of which 36 studies were finally analyzed. Most articles were retrospective studies based on panoramic radiographs. A delay in tooth development or -eruption in CL(P) patients was found in 32 out of the 36 included articles. The amount of delay varied from 0.20 to 0.90 years, with a mean delay of 0.56 years for all types of clefts. In UCLP patients, a mean delay of 0.53 years was found. The lateral incisor at the cleft side was generally the most delayed. Conflicting results were found regarding the influence of sex and age. The amount of delay was reported to be independent of the cleft severity or type. The teeth near the cleft generally showed a greater delay than the teeth further away from it. Finally, an increased risk of asymmetrical tooth development in CL(P) patients was observed in all publications studying this aspect. 31 articles were comparative, 5 were non-comparative; with a median MINORS score of 16/24 (range 10–18) and 10/16 (range 8–10) for both groups respectively. Conclusions: The majority of the included articles reports a delay in dental development or tooth eruption in CL(P) patients compared to non-CL(P) patients. The obtained results could be important for forensic age estimation outcomes and for orthodontic and surgical treatment planning in CL(P) patients. The delay in tooth development implies a delay in start of orthodontic treatment. Moreover, CL(P) patients could falsely be considered to be a minor when applying the existing reference tables for dental age estimation. Systematic review registration: International prospective register of systematic reviews (PROSPERO: CRD42018082106).